The relationship between organisational culture, market orientation and organisational performance in the food and beverage sector - Oliveira, Paulo Sergio Gonçalves de; Wada, Elizabeth Kioko; da Silva, Talita Galli; Machado, Claudia Leite; Mendes, Denise Coelho (Revista de Negócios, 2023)
The article’s objective was to evaluate how the organisational culture influences the market orientation and, consequently, the organisational performance of bars and restaurants in the city of São Paulo. To achieve the objective, the scale proposed by Jogaratnam (2017b) was adapted to the Brazilian reality and applied via Google Forms to professionals of bars and restaurants in the state of São Paulo, totalling 110 responses. Furthermore, the data were analysed by confirmatory factor analysis (PLS) through the SmartPLS version 3.2, which presented as significant the relationships between innovative culture and organisational performance, supportive culture and market orientation and organisational performance, demonstrating the aspects in which the food and beverage managers should pay attention to improve the performance of companies in the food and beverage sector, especially bars and restaurants.